2013
DOI: 10.1016/j.prevetmed.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind block randomized clinical trial on the effect of zinc as a treatment for diarrhea in neonatal Holstein calves under natural challenge conditions

Abstract: Diarrhea is the leading cause of death in neonatal calves and contributes to major economic losses. The objective of this double-blind randomized clinical trial was to evaluate the effect of oral inorganic or organic zinc supplementation as a treatment for neonatal diarrhea in calves. Seventy nine 1 to 8 day old male Holstein calves on a California calf ranch were block randomized to one of 3 treatments within 24h from their first onset of diarrhea. Calves received a daily dose of either a placebo composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
2
21
1
Order By: Relevance
“…107 g between treatment groups (Stata, College Station, TX). After allowing for 15% attrition and assuming 50% incidence of diarrhea based on study authors expert opinion, and a difference in ADG of 107g [11], a sample size of 500 calves per treatment group (n = 1500 total) was deemed required.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…107 g between treatment groups (Stata, College Station, TX). After allowing for 15% attrition and assuming 50% incidence of diarrhea based on study authors expert opinion, and a difference in ADG of 107g [11], a sample size of 500 calves per treatment group (n = 1500 total) was deemed required.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Zinc supplementation in children decreases the incidence, duration, and severity of diarrhea, increases recovery rates, decreases the use of antibiotics and antidiarrheal medications, and reduces mortality [5][6][7][8][9][10]. In a clinical trial that established a non-toxic zinc dose and investigated its therapeutic use for diarrhea in neonatal dairy calves, zinc-treated calves had numerically quicker clinical recovery, increased weight gain, and higher odds of fecal clearance of Cryptosporidium parvum between diarrhea onset and recovery compared with placebotreated calves [11]. As a result, zinc supplementation may be beneficial for prevention of diarrhea in dairy calves and, thus, minimize antimicrobial use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glover et al. () demonstrated that neonatal Holstein calves treated with a total daily dose of 80 mg of Zn (381.54 mg of Zn‐Met) did not exhibit clinical or laboratory evidence of Zn toxicity or mineral deficiency.…”
Section: Introductionmentioning
confidence: 99%